(untitled) (Studia Archaeologica, 2024)
During the 2017-2018 period, as part of the joint Mongolian-German project “Geomagnetic and pedestrian survey of Khar Khul Khan Balgas”, a discovery of 177 earthen mounds was made and documented in the Ulziit Denzh area of Erdenemandal Sum, Arkhangai Province. Further excavation work in 2018 focused on feature 172, leading to the uncovering of a unique burial site. Here, a female skeleton was found in an extraordinary position with an extreme crouched belly posture. Accompanying her were artifacts including a pebble axe and a pear-shaped pumice stone, all discovered at a depth of approximately 230 cm below the surface. Laboratory analysis of the human bone samples determined that the relic dates back 6,000. Notably, this burial represents a rare find in Mongolian archaeology, previously unseen in the region. Research findings of a unique archaeological study related to the Neolithic period called “Ulziit Denzh” were published in prestigious international journals, contributing significantly to the field of science. From 2021 to 2023, the scientific research project “Study of the extremely rare burial complex dating back to the 7th millennium in central Mongolia (Ulziit Denzh site)” was successfully carried out. This project led to the establishment of a protection zone for the archaeological site and the completion of thorough exploration and excavation. “Өлзийт дэнж” дурсгалын археологийн судалгааны үр дүн (2021-2023 он) Товчлол. 2017-2018 онд Монгол-Германы хамтарсан “Хархул хааны балгасны геомагнетик болон археологийн хайгуул судалгаа” төслийн хүрээнд Архангай аймгийн Эрдэнэмандал сумын нутаг Өлзийт дэнж хэмээх газарт 177 овгор шороон байгууламж илрүүлж бүртгэн баримтжуулсан юм. Улмаар 2018 онд 172-р байгууламжид археологийн сорилын малтлага гүйцэтгэж, 2.5 м гүнд толгойг нь баруун урагш хандуулан, биеийг нь атируулан түрүүлгэ нь харуулж, хайрган чулуун зэвсэг болон галт уулын уушгин чулуу дагалдуулсан 30-40 орчим насны эмэгтэй хүний оршуулга илрүүлсэн юм. Хүний ясны дээжид хийсэн лабораторийн судалгаагаар уг дурсгалыг одоогоос 6000 жилийн тэртээд холбогдохыг тогтоогоод байна. Энэхүү дурсгал нь Монгол нутгаас урьд өмнө нь илэрч байгаагүй, нэн ховор дурсгал болохыг тэмдэглэх нь зүйтэй бөгөөд археологийн шинжлэх ухаанд “Өлзийт дэнж” хэмээх шинэ чулуун зэвсгийн үед холбогдох өвөрмөц дурсгал нээгдэж, судалгааны үр дүнг олон улсын өндөр зэрэглэлийн сэтгүүлд нийтлэн эрдэм шинжилгээний эргэлтэд оруулсан юм. 2021-2023 онд “Монголын төв нутаг дахь VII мянган жилийн тэртээх нэн ховор оршуулгын цогцолборын судалгаа (“Өлзийт дэнж”-ийн дурсгал)” суурь судалгааны төслийг хэрэгжүүлж, дурсгалын хамгаалалтын бүсийг тогтоож, хайгуул, малтлага судалгааны ажлыг гүйцэтгээд байна. Түлхүүр үг. Өлзийт дэнжийн дурсгал, шороон байгууламж, шинэ чулуун зэвсгийн үе, хадгалалт хамгаалалт, малтлага, хайгуул судалгаа